Family-centered rehabilitation in high risk infant; A case report - Lulus Hardiyanti; Rizky Kusuma Wardhani; Aditya Rifqi Fauzi; . Gunadi (Universitas Gadjah Mada, 2022)
Preterm infants are categorized as a high-risk group in neonatology. Theyare physiologically less mature and have limited compensatory responsesto the extrauterine environment compared with term infants. Preterminfants need long-term evaluation, monitoring, and follow-up to optimizeneonatal care and development through an extensive rehabilitationperiod. However, the COVID-19 pandemic restricted patient care andfollow-up in the outpatient hospital setting. This case report discusses ahigh-risk infant treated with family-centered rehabilitation (FCR). Thepatient's rehabilitation issues included delays in gross motor, fine motor,and language development and preventing complications that may arisein a high-risk premature infant. Considering recent occurrences, ourapproach to rehabilitation programs for high-risk infants needs to bereevaluated and revised, focusing on home programs through familycentered treatment. These techniques may aid in delivering rehabilitationtreatments to children with developmental delays during COVID-19.